2022
DOI: 10.3389/fcimb.2022.937864
|View full text |Cite
|
Sign up to set email alerts
|

Potential Implications of the Lung Microbiota in Patients with Chronic Obstruction Pulmonary Disease and Non-Small Cell Lung Cancer

Abstract: Recently, chronic obstructive pulmonary disease (COPD) has been considered as a common risk factor of non-small cell lung cancer (NSCLC). However, very few studies have been conducted on the effects of COPD on the lung microbiota in patients with NSCLC. To identify the lung microbiota in patients with COPD and NSCLC (CN), the microbiome of the induced sputa of 90 patients was analyzed using 16S rDNA sequencing. The results showed no significant differences in the bacterial diversities of induced sputa among pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…Specific lung cancer-associated bacteria, such as Prevotella, may impact the tumor microenvironment and initiate a cascade reaction in cancer cells, leading to the upregulation of the PI3K/AKT signaling pathway and cancer development. Overall, this basic research reveals the potential role of Prevotella and other specific lung cancer-associated bacteria in lung cancer development, providing a possible avenue for researching new preventive and therapeutic strategies ( He et al., 2022 ). There is also a study that shows a potential association between Actinomyces and lung cancer development.…”
Section: Discussionmentioning
confidence: 97%
“…Specific lung cancer-associated bacteria, such as Prevotella, may impact the tumor microenvironment and initiate a cascade reaction in cancer cells, leading to the upregulation of the PI3K/AKT signaling pathway and cancer development. Overall, this basic research reveals the potential role of Prevotella and other specific lung cancer-associated bacteria in lung cancer development, providing a possible avenue for researching new preventive and therapeutic strategies ( He et al., 2022 ). There is also a study that shows a potential association between Actinomyces and lung cancer development.…”
Section: Discussionmentioning
confidence: 97%
“… 244 The abundance of Actinomyces was found to be significantly decreased after surgical operation in patients with NSCLC (non-small cell lung cancer). 253 Moreover, oral Actinomyces interacted strongly with methylation changes in immune genes, which was associated with patient prognosis. 254 Chua et al 255 conducted a study demonstrating that the increased abundance of Actinobacteria in the gut was associated with heightened immune activation among survivors of acute lymphoblastic leukemia (ALL) who experienced chronic inflammation.…”
Section: Overview Of Oral Microbiota In Carcinogenesismentioning
confidence: 99%
“…It was recognized that the microbial communities in many parts of the body are interconnected, including the mouth and the genital tract, and even the gastrointestinal tract and the genitourinary system [ 110 ]. As a result, scientists [ 110 , 111 ] demonstrated that bacteria are able to travel through the digestive tract and exchange ecological habitats with the intestines. Additionally, they found correlations between the vagina and the oral cavity.…”
Section: Antimicrobial Properties Of Microbial Biosurfactantsmentioning
confidence: 99%